Biting mechanics determines craniofacial morphology among extant diprotodont herbivores: dietary predictions for the giant extinct short-faced kangaroo, Simosthenurus occidentalis. Issue 1 (14th January 2019) - Mitchell, D. Rex; Wroe, Stephen
Abstract: Large herbivores can act as keystone species that strongly influence their communities. During the Pliocene and Pleistocene, Australia was dominated by a number of large to gigantic marsupial herbivore taxa. Many of these have been understudied quantitatively with regard to their ecology; and identifying the diet of these species will improve our understanding of not only their ecologies, but also of past environments. Recent research has found that cranial morphology among kangaroos and wallabies corresponds with foraging behaviors and mechanical properties of preferred plant tissues. Here we apply shape analysis and computational biomechanics to test the hypothesis: that feeding ecology is associated with craniofacial morphology across a taxonomically broad sample of diprotodont herbivores. Based on our results we predict the diet of an extinct short-faced kangaroo, Simosthenurus occidentalis . We find that biting behaviors are reflected in craniofacial morphology, but that these are more a reflection of the hardest bites required for their lifestyle, rather than diet composition alone. A combination of a very short face, robust musculoskeletal features, and dental arrangements predict that S. occidentalis was a browser, capable of consuming particularly resistant, bulky plant matter. These features were largely conserved among other short-faced kangaroos and may have offset the unpredictable availability of quality forage during the climatically variable Pleistocene epoch, contributing to their prolific diversification during this time.